Electoral Effects of Biased Media: Russian Television in Ukraine. Issue 3 (30th March 2018) - Peisakhin, Leonid; Rozenas, Arturas
Abstract: We use plausibly exogenous variation in the availability of the Russian analog television signal in Ukraine to study how a media source with a conspicuous political agenda impacts political behavior and attitudes. Using highly disaggregated election data and an original survey, we estimate that Russian television substantially increased average electoral support for parties and candidates with a "pro‐Russian" agenda in the 2014 presidential and parliamentary elections. Evidence suggests that this effect is attributable to persuasion rather than differential mobilization. The effectiveness of biased media varied in a politically consequential way: Its impact was largest on voters with strong pro‐Russian priors but was less effective, and to some degree even counter‐effective, in persuading those with strong pro‐Western priors. Our finding suggests that exposing an already polarized society to a biased media source can result in even deeper polarization.